Combined Ultrasound and CT-Guided Iodine-125 Seeds Implantation for Treatment of Residual Hepatocellular Carcinoma Located at Complex Sites After Transcatheter Arterial Chemoembolization - Ren, Yanqiao; Dong, Xiangjun; Chen, Lei; Sun, Tao; Alwalid, Osamah; Kan, Xuefeng; Su, Yangbo; Xiong, Bin; Liang, Huimin; Zheng, Chuansheng; Han, Ping (Frontiers in Oncology, 2021)
Purpose The purpose of this study was to evaluate the efficacy and safety of iodine-125 (125I) seeds implantation under ultrasound and computed tomography (CT) guidance in the treatment of residual hepatocellular carcinoma (HCC) located at complex sites after transcatheter arterial chemoembolization (TACE). Methods This retrospective study analyzed the consecutive medical records of 31 HCC patients with residual tumors located at complex sites (such as large blood vessels, gallbladder, diaphragm dome, etc.) after TACE from May 2014 to December 2018, all of whom received 125I seeds implantation therapy. Overall survival (OS), progression-free survival (PFS), recurrence, and complications were documented. Results A total of 607 seeds were implanted in 31 patients, with an average of 19.6±10.4 (range, 8–48) seeds per patient. Median OS and PFS were 33 months (95% CI: 27.1 months, 38.9 months) and 15 months (95% CI: 9.6 months, 20.4 months), respectively. Although univariate analysis showed that albumin, prothrombin time, alpha-fetoprotein level, Child-Pugh score, and lipiodol deposition in tumor were associated with OS, multivariate analysis showed that none of them was an independent prognostic factor for OS. Multivariate analysis showed that prothrombin time was an independent prognostic factor for PFS. No operation-related deaths in this study. Although pneumothorax was present in two patients and subcutaneous abscess in one patient, symptoms improved in all three patients with appropriate treatment. Common minor complications included fever, abdominal pain and leukopenia and no grade≥3 adverse events were observed. Conclusions 125I seeds implantation under the combined guidance of ultrasound and CT is safe and effective for patients with residual HCC located at complex sites after TACE. This is a promising treatment approach and deserves further discussion.